Pengaruh Permainan Tradisional Gobak Sodor terhadap Kelincahan Gerak Atlet Bola Basket Putri U-14 Klub Lotus Wonosobo - Putri, Salma Harienda; Pujianto, Agus (Universitas Negeri Semarang, 2023)
In this gobak sodor game, there are elements of courage, honesty, cooperation between players, and also agility. This basketball game is a fast game and requires good agility, so high agility is needed in order to do a good defense and dribbling position. This agility component is suitable to be mastered more by a basketball athlete because the size of a basketball court that is not so wide requires a player to move as fast a possible when passing his opponent by dribbling. Researchers used a pre-experimental research method with a one group pretest posttest design. The sampling technique used was Purposive Sampling, namely sampling with certain considerations and criteria, with a total sample of 20 samples. The results of data analysis using the Normality Test, Homogeneity Test and hypothesis testing with the T test. The results of the study after the data were analyzed were that there was a significant influence with the results of the t test calculations obtained a value of 8.948 and t-table 2.093 with a sig value of 0.000 <0.05. So that Ha can be accepted. The conclusion of this study is that the traditional game of gobak sodor can affect the agility abilities of female u-14 basketball athletes at the Lotus Wonosobo club, and is expected to become a training method that can be used by coaches to improve the agility of athletes.